THE INFLUENCE OF THIRD PARTY FUNDS, NON PERFORMING FINANCING, AND CAPITAL ADEQUACY RATIO ON PROFITABILITY WITH PROFIT SHARED FINANCING AS AN INTERVENING VARIABLE AT BANK MUAMALAT INDONESIA PERIOD 2014-2021 - Zainuddin Saleh Lubis; Nurlaila Nurlaila (Jurnal Ekonomi, 2023)
This study aimed to assess the impact of third party funds, non-performing financing, and capital adequacy ratio on Bank Muamalat Indonesia's profitability with financing as an intervening variable for the period 2014-2021. This is quantitative study employing an associative methodology. This study's population utilized 32 quarterly financial reports from BUS companies in Indonesia. Data acquired from the website of Bank Muamalat Indonesia. The sample approach utilized in this study was purposive sampling. While data collection procedures are derived from Bank Muamalat Indonesia's data, The classical assumption test, simple and multivariate regression analysis, path analysis, and hypothesis analysis are utilized for the data analysis. The results demonstrated that DPK has a considerable direct effect on profit sharing financing, as indicated by the tcount value of 2.368> t table 2.04227 and the significance of the t test value of 0.025 0.05. The NPF test on profit sharing financing yielded a tcount value of -1.030 t table 2.04227 and a significant t test value of 0.312 0.05, demonstrating that NPF has no direct influence on profit sharing financing. This is indicated by the CAR test on profit sharing financing, which yields a tcount value of 2.741> t table 2.04227, indicating that there is an effect of CAR on profit sharing financing and a significant value of 0.011 0.05 for the t test.